Electrosynthesis of ethylene glycol from biomass glycerol - Haoyuan Chi; Zhanpeng Liang; Siyu Kuang; Yaxin Jin; Minglu Li; Tianxiang Yan; Jianlong Lin; Shuangyin Wang; Sheng Zhang; Xinbin Ma (Nature Communications)
Abstract Ethylene glycol, a widely used chemical, has a large global capacity exceeding 40 million tons per year. Nevertheless, its production is heavily reliant on fossil fuels, resulting in substantial CO2 emissions. Herein, we report an approach for electrochemically producing ethylene glycol from biomass glycerol. This process involves glycerol electrooxidation to glycolaldehyde at anode, which is subsequently electro-reduced to ethylene glycol at cathode. While the anode reaction has been reported, the cathode reaction remains a challenge. An electrodeposited electrode with metallic Cu catalyst enables us to achieve glycolaldehyde-to-ethylene glycol conversion with an exceptional faradaic efficiency of about 80%. Experimental and theoretical studies reveal that metallic Cu catalyst facilitates the C=O activation, promoting glycolaldehyde hydrogenation into ethylene glycol. We further assemble a zero-gap electrolyzer and demonstrate ethylene glycol electrosynthesis from glycerol to give a decent production rate of 1.32 mmol cm–2 h–1 under a 3.48 V cell voltage. The carbon intensity assessment based on a valid assumption reveals that our strategy may reduce CO2 emissions by over 80 million tons annually compared to conventional fossil fuel routes.